The Correlation Between Lipid Profile and Xanthelasma - Puridelko Kampar; Qaira Anum; Sri Lestari (Department of Dermatology and Venereology, Faculty of Medicine, Universitas Airlangga, 2020)
Background: Xanthelasma is an abnormal lipid deposition on palpebrae, which is observable as yellowish plaque or nodules. Its incidence is 0.56-1.5% with onset of 15-73 years old and mostly occurs in the fourth and fifth decade. Few reports of xanthelasma did not cover the correlation between lipid profile and xanthelasma in Indonesia. Purpose: To find a correlation between lipid profile with xanthelasma in Dr. M. Djamil Hospital, Padang. Methods: This was an analytic cross-sectional study with consecutive sampling. There were 36 participants (18 xanthelasma and 18 control). Result: The highest age group was >36 - ≤45 years old (38.89%). More cases were observed in female (66.67%). Body mass index examination of xanthelasma revealed that most were overweight (55.56%). Grade I xanthelasma was the most common (72.22%). The cholesterol serum level of xanthelasma patients was higher than the subject controls (224.61±29.77 mg/dl versus 169.39±35.84 mg/dl) (p<0,05). The High Density Lipoprotein (HDL)  serum level of xanthelasma patients was lower than controls (46.44±14.19 mg/dl versus 51.78±15.9 mg/dl) (p>0,05). The Low Density Lipoprotein (LDL) serum level of xanthelasma patients was higher than control (139.39±29.73 mg/dl versus 106.50±35.43 mg/dl) (p<0,05). Triglyceride serum level of xanthelasma patients was higher than the controls (167.83±87.26 mg/dl versus 121.61±54.52 mg/dl) (p>0,05). Conclusion: There was a correlation between higher cholesterol and LDL serum level with xanthelasma. No correlation between lower HDL and a higher triglyceride serum level with xanthelasma.